'Should I stay or should I go?' Group-analytic training: inhabiting the threshold of ambivalence is a matter of power, privilege and position. (March 2021) - Forrest, Alasdair; Nayak, Suryia
Having in mind those gripped by ambivalence over whether to start, or stay on, the Qualifying Course in Group Analysis, we consider the training as one in ambivalence. We see ambivalence as an asset, not a hindrance. Forsaking familiar notions of ambivalence as weak and anxious, the task is to move towards a confident ambivalence. Using the ambivalent etymology of the word 'threshold' as an analytic lens, we use threshold not in the sense of a wooden solid boundary to be overcome, but rather as a threshing room. This article is co-written by two people different in terms of race, gender, sexuality, socio-economic background, age and experience. We argue that understanding the relationship between difference and ambivalence is crucial. This is not only because difference matters in itself. This article argues that ambivalence finds separate expressions through these differences, which act as a symbolic site. Our experience as Manchester trainees proves that threshing of the wheat from the chaff cannot happen on seemingly rigid boundaries. Rather, it happens in thresholds. In all this, examining the way ambivalence functions through power, privilege and position, we return to the ambivalent question: Do you want group analysis? And does it want you?